Lesson planning: secondary pre-service teachers’ cognitions and declared practices - Wanlin, Philippe (Swiss Journal of Educational Research, 2018)
Lesson planning is an important factor to favor effective teaching. This text suggests a short overview of two orientations followed by research on teachers’ planning thought processes. This resume leads to three research questions that are investigated by means of an opinion poll of a sample of 73 pre-service teachers graduating for secondary education in Geneva. Results lead to conclusions contrasting with existing research literature based on case studies or reduced samples of teachers. The differences are discussed in terms of follow through research and of implication for teacher education.